Strategic Assessment of Solid Waste Management Services and Systems in Nepal : Policy Advisory Note - World Bank (World Bank, Washington, DC, 2020)
This report Strategic assessment of solid waste management services and systems in Nepal is prepared by the World Bank Team in consultations with various Government agencies and Development Partners. These stakeholders had provided rich and detailed input throughout the process, prioritized the selection of study areas, and provided guidance on the initial and final findings and recommendations of the report.